2020
DOI: 10.1590/0034-7167-2018-0921
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous access using devices over needles with and without extension: costs and outcomes

Abstract: Objectives: to analyze the mean direct cost and peripheral venous access length outcomes using devices over needle with and without extension. Methods: quantitative, exploratory-descriptive research. Venous punctures and length of the devices were followed. The mean direct cost was calculated by multiplying the time (timed) spent by nursing professionals by the unit cost of labor, adding to the cost of materials. Results: the total mean direct cost of using devices “with extension” (US$ 9.37) was 2.9 times t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the current study, the 22-gauge device was the majority in both groups, as well as in another study 5. Published data point out that the appropriate choice of gauge is a decisive factor for the successful establishment of the PIVC in the first cannulation attempt 21. In the present study, there was no significant difference between the gauge and the development of phlebitis, unlike the study by Simin et al,15 who reported that the 22-gauge catheter was 5.8 times more likely to develop phlebitis, the 20-gauge 11.3 times, and the 18-gauge 12.1 times.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the 22-gauge device was the majority in both groups, as well as in another study 5. Published data point out that the appropriate choice of gauge is a decisive factor for the successful establishment of the PIVC in the first cannulation attempt 21. In the present study, there was no significant difference between the gauge and the development of phlebitis, unlike the study by Simin et al,15 who reported that the 22-gauge catheter was 5.8 times more likely to develop phlebitis, the 20-gauge 11.3 times, and the 18-gauge 12.1 times.…”
Section: Discussionmentioning
confidence: 99%